Modern regionalism approach in designing contemporary Djami' Mosque for sustainable communal development / Alice Sabrina Ismail and Suhaila Mohd Siraj - Alice Sabrina, Ismail; Mohd Siraj, Suhaila (Universiti Teknologi MARA, Perak, 2021)
Modern regionalism approach is essential because it can contribute to the context of Malaysia's development in creating an architecture that respects the local context, as well as foster unity and integration among the community. Besides that, it can produce a built environment that is easily recognized to portray progressive values and achievement of the national civilization in line with the needs of the society and sustainable environment. However, most mosque designs in the current Malaysian context show less awareness of the approach and values of modern regionalism. As a result, most of the newer mosque features grand appearance with eclectic and Middle East revivalism approach and less on its role towards meeting users' sustainable needs. Therefore, the objective of this paper is to identify and analyze the characteristics and elements which favours the modern regionalism approach in djami' mosques for sustainable communal development. This study used the hermeneutic method through the interpretivism paradigm. The two indicators of modern regionalism which are the contextual and tectonic factors are for analyzing the djami' mosque design. The findings showed that for a mosque design with regionalism characteristics for sustainable communal development, it must meet the requirements of local climate, topography, and culture in line with current times. Based on these findings, contribution in the form of djami' mosque design proposal from the context and tectonic factors are of benefit for future designers towards a sustainable built environment and communal development in Malaysia.